1988
DOI: 10.1113/jphysiol.1988.sp017207
|View full text |Cite
|
Sign up to set email alerts
|

Reflex tracheal contraction during pulmonary venous congestion in the dog.

Abstract: SUMMARY1. The effect of pulmonary venous congestion on tracheal tone was studied in dogs anaesthetized with ax-chloralose. Pulmonary venous congestion was produced by partial obstruction of the mitral valve to increase left atrial pressure by 10 mmHg. Tracheal tone was measured in vivo by an isometric force displacement method.2. Tracheal tone increased by 63 + 03 g from a control level of 91-6 + 2-8 g when left atrial pressure was increased by 10-5 + 0-3 mmHg. This response was abolished by cooling the cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Several studies have suggested that airway narrowing during pulmonary congestion was vagally-mediated, because airway obstruction during pulmonary congestion was abolished with either atropine or vagotomy [8][9][10]. However, pretreatment with a dose of atropine that totally blocks muscarinic receptor activity [32] does not affect the increase in canine Rp associated with volume loading in our model.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Several studies have suggested that airway narrowing during pulmonary congestion was vagally-mediated, because airway obstruction during pulmonary congestion was abolished with either atropine or vagotomy [8][9][10]. However, pretreatment with a dose of atropine that totally blocks muscarinic receptor activity [32] does not affect the increase in canine Rp associated with volume loading in our model.…”
Section: Discussionmentioning
confidence: 39%
“…However, pretreatment with a dose of atropine that totally blocks muscarinic receptor activity [32] does not affect the increase in canine Rp associated with volume loading in our model. This difference may be due to either: 1) differences between canine trachea and peripheral airway [10]; 2) differences in the time of treatment (we pretreated with atropine whereas the other investigators used this drug to reverse pulmonary congestion [8,9]); or 3) differences in protocols, e.g. ISHII et al [6] abruptly increased left atrial pressure by inflating a balloon to 30 mmHg, whereas we gradually increased PCWP to 15 mmHg with a 20 min infusion of normal saline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, one vagus was intact and the other, from which recordings were made, was partly so. The increase observed in peak intratracheal pressure during congestion could be due to (a) a passive stiffening of the lung due to vascular congestion, (b) a reflex bronchoconstriction (Kappagoda, Man, Ravi & Teo, 1988) and (c) a combination of the above. An earlier study examined the effect of bilateral vagotomy on the peak intratracheal pressure changes observed during pulmonary vascular congestion (Kappagoda et al 1987).…”
Section: Lymphflowmentioning
confidence: 99%
“…Authors have addressed the mechanisms responsible for bronchial narrowing in animal models of pulmonary edema. Results variably support a role for reflex vagal efferent tone [3, 7, 9, 10, 11]and the development of airway epithelial edema and peribronchial cuffing [1, 2, 3, 6, 7, 8, 12, 13, 14, 15]. Don and Johnson [13]observed a correlation between airway narrowing on chest radiographs and mucosal edema on histologic examination of human lungs.…”
Section: Introductionmentioning
confidence: 99%